2020
DOI: 10.1016/s1473-3099(20)30278-4
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of M1UK clade among Dutch M1 Streptococcus pyogenes

Abstract: difference was not significant (Fisher's exact test, p=0•39).In summary, the M1 UK lineage was seen in diverse geographic regions, formed a local disease cluster, and caused severe infection syndromes in the USA from 2015 to 2018. Although this clone did not expand substantially according to data in the ABCs system, continued genomic surveillance is needed to monitor the effects of this and other emerging virulent strains.We declare no competing interests. The findings and conclusions of this Correspondence ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…The emergence of the M1 UK lineage in the UK and its detection in other countries 19,[21][22][23] triggered our investigation of 318 Australian emm1 S. pyogenes isolates. Overall 310/318 were invasive isolates from sterile body sites and sourced from state-based public health laboratories in Queensland and Victoria between 2005 and 2020.…”
Section: Detection Of Streptococcus Pyogenes M1 Uk In Australiamentioning
confidence: 99%
“…The emergence of the M1 UK lineage in the UK and its detection in other countries 19,[21][22][23] triggered our investigation of 318 Australian emm1 S. pyogenes isolates. Overall 310/318 were invasive isolates from sterile body sites and sourced from state-based public health laboratories in Queensland and Victoria between 2005 and 2020.…”
Section: Detection Of Streptococcus Pyogenes M1 Uk In Australiamentioning
confidence: 99%
“…Despite differing from older emm 1 strains by just 27 core genome SNPs, the new sublineage was characterised by a ~ten-fold increase in expression and production of the superantigen SpeA. Since 2019, the M1 UK lineage has been identified elsewhere in Europe and North America (57).…”
Section: Introductionmentioning
confidence: 98%
“…Lynskey et al (2019) showed that the toxigenic M1T1 clone (M1T1 UK ) is related to the increased incidence of invasive GAS disease in the United Kingdom. Thereafter, the M1T1 UK strain was identified in Canada, the Netherlands, and the United States (Demczuk et al, 2019;Li et al, 2020b;Rumke et al, 2020), demonstrating the possibility of clonal expansion of the M1T1 UK clone. In Taiwan, Yan et al (2000) showed that 64.3% erythromycin-resistant isolates were clindamycin-susceptible and harbored mefA before 1998.…”
Section: Discussionmentioning
confidence: 99%